Strukturalne cechy bezrobocia w województwie dolnośląskim - Sucholiński, Andrzej (Structural Features of Unemployment in Lower Silesia, 2005)
In the article the author tries to show the level of unemployment as well as its structural features in Lower Silesia between 1998 and 2002. From the point of unemployment policy in regional and lo-cal areas it is important to identify certain unemployment groups: the long-termunemployed, the unemployed caused by group layaffs, the unemployed who have no right to receive unemployment benefit, the unemployed graduates, the unemployed who live in villages, disabled people and others.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 142-153